KUANTITASI DAN IDENTIFIKASI BAKTERI ASAM LAKTAT SERTA KONSENTRASI ASAM LAKTAT DARI FERMENTASI IKAN GABUS (Channa striata), IKAN NILA (Oreochromis niloticus), DAN IKAN SEPAT (Trichogaster trichopterus) PADA PEMBUATAN BEKASAM - Novianti, Dewi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2013)
This study aims to determine the quantitation of lactic acid bacteria and lactic acid bacteria as well as identify the concentration of lactic acid produced from fermented catfish (Channa striata), tilapia (Oreochromis niloticus), and fish Sepat (Trichogaster trichopterus) on maked bekasam (fish fermented). This research was conducted at the Center for Health Laboratory Palembang on July till August 2009 . Research used titrimetric method for determining the levels of lactic acid. Total Plate Count method to determine the amount of lactic acid forming bacteria, while the identification of lactic acid bacteria is done through biochemical tests and test the differential characteristics of lactic acid forming bacteria . The highest content of lactic acid bacteria is 124.904 x 103 colonies/ml and the highest levels of lactic acid is 6.363% derived from Sepat fermented fish. Sepat fermented fish and tilapia on making bekasam found lactic acid bacteria of the genus Lactobacillus sp, Pediococcus sp and Streptococcus sp. While the results of fermentation bekasam found only in fish cork lactic acid bacteria of the genus Lactobacillus and Streptococcus sp. Key words: fermentation, bekasam, identification, lactic acid bacteria,